The Determinants of FDI in BRIC countries - Lu, Wenbo (2012)
The combined economies of Brazil, Russia, India, and China (BRIC) have attracted more and more Foreign Direct Investment (FDI) and developed rapidly. This Study examines the determinant factors of FDI inflows into BRIC countries using a set of Panel data from 2001 to 2011. The study conducts panel data analysis and finds the variables as Market Size, Inflation Rate, Labor Cost, Trade Openness, Currency Value and Political Risk are potential determining factors of FDI inflows to BRIC countries. The result suggests that Market Size (measured by GDP per capita), Labor Cost (measured by Wages), and Trade Openness (measured by the ratio of FDI inflows to GDP) are positive and significant in relation to FDI inflows. Inflation Rate and Currency Value (measured by exchange rate) have negative significant effects on FDI inflows to BRIC countries. Trade Openness is an insignificant determinant factor of FDI inflows to BRIC economies.